Definisi, Penyebab, Klasifikasi, dan Terapi Sindrom Dispepsia - Wildani Zakiyah; Annastya Eka Agustin; Annisa Fauziah; Nur Sa’diyyah; Galih Ibnu Mukti (Syntax Corporation Indonesia, 2021)
Dyspepsia is a symptomatic syndrome disease characterized by pain or discomfort in the upper part or heartburn. Organic dyspepsia is caused by disorders in the gastrointestinal tract or around the gastrointestinal tract, such as the pancreas, gallbladder and others. The purpose of this study is to find out the definition, causes, classification, and therapy of dyspepsia syndrome. The method used in reviewing this article is the collection of literature from existing journal sources related to dyspepsia in general sourced from google, google scholar, and e-book using the keywords